Effect of final irrigant on depth of tubular penetration of resin-based root canal sealer and bioactive sealers using confocal laser scanning microscope - Shruti Singh Kanwar; Sonali Taneja; Pragya Kumar; Chetna Dudeja (Wolters Kluwer Medknow Publications, 2020)
Background: Deep dentin tubular penetration of the sealer provides a three dimensional sealing of root canal space Aim: To evaluate the effect of final irrigant on depth of tubular penetration of resin based root canal sealer and bioactive sealers using Confocal Laser Scanning Microscope (CLSM) Materials and Method: Ninety- six freshly extracted human mandibular first premolar teeth were decoronated at 15 mm from the apex. Cleaning and shaping procedure was accomplished using Hyflex CM rotary files till F3. The sample were divided into three groups(n=32) according to final irrgant used : Group A (17 % EDTA), Group B (QMix 2 in 1), Group C (Distilled water). The final irrigation in each respective group was performed with EndoVac system. The samples were further subdivided into 4 subgroups (n=8) according to the type of sealer used for obturation with 6% guttapercha cones - Subgroup I (AH Plus), Subgroup II (Gutta Flow Bioseal), Subgroup III ( Endosequence BC ), Subgroup IV (EndoSeal MTA). Two mm horizontal sections were obtained at 2 mm (apical sections), 5 mm (middle sections) and 7 mm (coronal sections) from the root apex using CLSM to evaluate the maximum depth and percentage of sealer penetration into the dentinal tubules by using Kruskal-Wallis test for overall analysis and a series of Mann-Whitney U tests for pairwise comparison. Result: Endosequence BC showed maximum depth of penetration and penetrated percentage perimeter, while Gutta Flow Bioseal showed least values. Q Mix 2 in 1 showed better penetration values than EDTA and distilled water. Conclusion: Irrigants, nature of sealer and level of root canal affected sealer penetratio.